Blastomycosis Presenting as Multiple Splenic Abscesses: Case Report and Review of the Literature. Issue 1 (2010) - Al-Nassar, Sami; MacNair, Tracy; Lipschitz, Jeremy; Greenberg, Howard; Trepman, Elly; Hamza, Sate; Embil, John M
Abstract : A 31-year-old Canadian Aboriginal man from northwestern Ontario presented with left upper quadrant pain and a tender left upper quadrant mass. Evaluation with a computed tomography scan showed multiple lesions within the spleen, a collection between the splenic tip and splenic flexure of the colon, and several small adrenal lesions. Computed tomographic-guided needle biopsy showed necrotizing granulomatous inflammation and multinucleated giant cells. Gomori's methenamine silver stain showed broad-based budding yeast consistent with Blastomyces dermatitidis . Abdominal symptoms resolved after two months of oral itraconazole. Multiple splenic abscesses are a rare presentation of blastomycosis and should be considered in the differential diagnosis of left upper quadrant abdominal pain in a patient with a history of travel or residence in a region endemic for B dermatitidis .